2010
DOI: 10.1002/gj.1226
|View full text |Cite
|
Sign up to set email alerts
|

Major, minor element chemistry and oxygen and hydrogen isotopic compositions of Marun oil‐field brines, SW Iran: Source history and economic potential

Abstract: Cation and anion concentrations and oxygen and hydrogen isotopic ratios of brines in the Asmari Formation (Oligocene-early Miocene) from the Marun oil field of southwest Iran were measured to identify the origin of these brines (e.g. salt dissolution vs. seawater evaporation) as well as the involvement of water-rock reaction processes in their evolution. Marun brines are characterized by having higher concentrations of calcium (11 000-20 000 mg/L), chlorine (120 000-160 000 mg/L) and bromide (600-1000 mg/L) co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(2 citation statements)
references
References 43 publications
(54 reference statements)
0
2
0
Order By: Relevance
“…As mentioned earlier, MWLs developed for the dominant Iran moisture sources can be used in the study of moisture source contribution rate in karstic springs and surface water resources recharge. Surface water resources isotope data were collected from three dominant zones in the north of Iran, west Zagros and south Zagros [17,18,20,43,54,57,62,67,68,[74][75][76][77][78][79][80][81][82][83][84][85] and presented in Supplementary Table S4. To study the role of the dominant moisture sources in surface water resources recharge, surface water samples were plotted on the Caspian Sea, the Persian Gulf and the Mediterranean Sea MWLs (Figure 7).…”
Section: Mwls For Specific Moisture Sourcesmentioning
confidence: 99%
“…As mentioned earlier, MWLs developed for the dominant Iran moisture sources can be used in the study of moisture source contribution rate in karstic springs and surface water resources recharge. Surface water resources isotope data were collected from three dominant zones in the north of Iran, west Zagros and south Zagros [17,18,20,43,54,57,62,67,68,[74][75][76][77][78][79][80][81][82][83][84][85] and presented in Supplementary Table S4. To study the role of the dominant moisture sources in surface water resources recharge, surface water samples were plotted on the Caspian Sea, the Persian Gulf and the Mediterranean Sea MWLs (Figure 7).…”
Section: Mwls For Specific Moisture Sourcesmentioning
confidence: 99%
“…In preliminary studies have been observed that formation waters of all oil and gas production basins in the world (including Southeastern Anatolia basin and Thrace basin) are contained >1 mg/L iodine (USGS Produced Water Database; Engle et al, 2016;Oppo et al, 2014;Oppo and Capozzi, 2015;Sudo, 1967;Kaiho, 2015;Kharaka et al, 1987;Dia et al, 1999;Dresel andRose, 2010, Rowan et al, 2015;Mirnejad et al, 2011;Xun et al, 1997;Fisher and Kreitler, 1987;Dickey et al, 1972;Land, 1995;Birkle et al, 2002;Birkle et al, 2009;Franks and Uchytil, 2016;Hitchton et al, 1971;Machperson, 1992;Kokh and Novikov, 2014;Novikov, 2013a, b;Novikov, 2012;Novikov and Shvartsev, 2009, Demir and Seyler, 1999, Kurchikov and Plavnik, 2009, Fu and Zhan, 2009, Kireeva, 2010, Bagheri et al, 2014. However, there are also production wells with formation waters containing iodine <1 mg/L in Southeastern Anatolia and Thrace basins (Appendix-1), Dörtyol (Hatay) gasfi eld, Cambay basin/India (Rebary et al, 2014) and in basins of other global oil and gas fi elds.…”
Section: Source Of Iodine In Waters and Iodine Contents Of Waters Assmentioning
confidence: 99%